Interactivity on Government Social Media to Improve Public Services - Aji, Gilang; Sukardani, Puspitasari; Setianingrum, Vinda Maya; Indrajayani, Galuh Gita (COMMENTATE: Journal of Communication Management, 2023)
Social media is considered to be able to support public service activities by the government by encouraging transparency, creating interaction with citizens, and building collaboration with citizens. The key must be to build an interactive relationship between the government (the organizer of the state authority) and the community. The problem is that our social media has not been used enough for interaction or even only aims to communicate one way. This research is an advanced stage of various previous studies on the use of social media for the Government, especially local governments. There is a tendency to direct the object not on the main government account to become a more specific agency/agency in charge of public services. The researcher wants to see the interactive pattern that occurs on Instagram @dishubsurabaya which is managed by the Surabaya transportation service in order to provide better service. The research was conducted using a case study method by extracting data through interviews with both parties: the government and citizens. The results show that agencies and citizens benefit together when they can connect. To achieve this, the first step is to build a new creative message and then seek interactivity with the availability of a team that is always ready to respond to questions and complaints.